2015
DOI: 10.1002/ejoc.201501228
|View full text |Cite
|
Sign up to set email alerts
|

High‐Yielding Synthesis and Full Spectroscopic Characterization of 5,6:11,12‐Di‐o‐phenylenetetracene and Its Synthesis Intermediates

Abstract: Herein we present a synthetic gram-scale route to 5,6:11,8), which is a member of the class of cyclopenta-fused polycyclic aromatic hydrocarbons (CP-PAHs). Full analytical characterization of the title compound was carried out by IR, Raman, UV/Vis, and high-field 1 H NMR spectroscopy, as well as by mass spectrometry. A unique double-elimination of phenylide moieties, as the key reaction step, gave DOPT for the first time in high purity and

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
23
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 17 publications
(23 citation statements)
references
References 50 publications
(65 reference statements)
0
23
0
Order By: Relevance
“…Finally,w eg ive evidence towards the dependence of its electronic thin film transistor properties on the deposited film density.A ccording to our finding,r eductive elimination of two phenyl rings from the dihydrotetracene derivative 5,12-diphenyl-5,6;11,12-di-o-phenylene-5,12-dihydrotetracenepseudorubrene) 1 under re-aromatization has yielded DOPT 2 in high yield on ag ram scale. [5] As an extension of these studies we now report on the molecular structure of 2.W ehave found that it crystallizes at least in two polymorphic crystal arrangements depending on the crystallization procedures employed. Growth from aconcentrated tetrahydrofuran or toluene solution gives single crystals of DOPT which crystallize in space group C 2/c, whereas slow thermal gradient sublimation gives deep blue, primitive monoclinic crystals of space group P 2 1 /n (see Supporting Information).…”
mentioning
confidence: 94%
See 2 more Smart Citations
“…Finally,w eg ive evidence towards the dependence of its electronic thin film transistor properties on the deposited film density.A ccording to our finding,r eductive elimination of two phenyl rings from the dihydrotetracene derivative 5,12-diphenyl-5,6;11,12-di-o-phenylene-5,12-dihydrotetracenepseudorubrene) 1 under re-aromatization has yielded DOPT 2 in high yield on ag ram scale. [5] As an extension of these studies we now report on the molecular structure of 2.W ehave found that it crystallizes at least in two polymorphic crystal arrangements depending on the crystallization procedures employed. Growth from aconcentrated tetrahydrofuran or toluene solution gives single crystals of DOPT which crystallize in space group C 2/c, whereas slow thermal gradient sublimation gives deep blue, primitive monoclinic crystals of space group P 2 1 /n (see Supporting Information).…”
mentioning
confidence: 94%
“…[1,2] In the group of cyclo-pentafused polycyclica romatic hydrocarbons (PAH) 2 represents aprototypical acene framework molecule with peri-substitution closely related to tetracene,5,6,11,12-tetraphenyltetracenerubrene,orthe di-ophenylene substituted anthracene molecule rubicene. [2] Although, reported earlier in elusive experimental work [3] it was only very recently,that DOPT 2 was made accessible by Murata [4] and our group [5] in two independent and straightforward high yield synthetic approaches.Murata et al presented ag eneral approach towards cyclo-pentafused polycyclic aromatics including DOPT-derivatives starting from the 5,11-diaryl-tetracene framework.[4] Shortly after,w ew ere able to devise agram-scale synthesis based on well established Diels-Alder chemistry for the parent molecule DOPT introducing as of ar unprecedented reductive double phenyl elimination.[5] Highly condensed PA Hm olecules like DOPT with their oftentimes energetically favorable molecular orbital ordering with small electronic band gap differences excel themselves as promising semiconducting organic materials for controlled charge transport. Thea fore mentioned close structural relationship of DOPT to the polyacene aromatic family especially the parent tetracene might promise interesting functional properties applicable in organic electronics like thin film transistors or future solar energy harvesting devices.…”
mentioning
confidence: 98%
See 1 more Smart Citation
“…22 Saturated solutions of DOPT in dichloromethane (DCM) were prepared by dissolving 2 mg DOPT in 10 mL DCM. Needle-like crystals were deposited on individual substrates by simple drop coating of the as-prepared solution (Fig.…”
Section: Materials and Preparation Of Substratesmentioning
confidence: 99%
“…21 Herein, we demonstrate synthesis, characterization and sensoric behaviour of carbon nanobers with an amorphous structure (a-CNFs) by thermal conversion of the recently available cross conjugated tetracene molecule 5,6;11,12-di-ophenylenetetracene (DOPT, 3). 22, 23 The obtained a-CNFs were studied towards their functional properties in a chemiresistor device for the detection of toxic gases. For this, nitrogen dioxide, ammonia and sulfur dioxide were chosen as analyte gases.…”
Section: Introductionmentioning
confidence: 99%